P51 Follow-up of the incidental pulmonary nodule outcomes and costs. (14th November 2013) - Harper, J; Marchand, C; Bevan, H; Masani, V; Suntharalingam, J
Abstract : A retrospective study to analyse the outcomes and costs of follow-up of incidental nodules (solitary and multiple) referred to our Department from 2010 2011. Method: Consecutive nodule cases were identified by reviewing CT reports of 619 patients discussed at our Lung Cancer MDT from 2010 2011. Only clinically incidental nodules were included. Information was gathered using PACS and hospital records. In our department incidental nodules are seen once in clinic and then largely managed 'remotely' via correspondence. All nodules are managed to Fleischner guidelines. Costs for investigations/procedures/appointments were calculated using local 2012 13 reference costs. Manpower costs for MDTs and correspondence were calculated using a 'bottom-up' costing approach. Results: 62 patients were referred with a new incidental nodule (s). Mean age was 66(34 92) with a 1:1 male:female ratio. 56%(35/62) had PS 0 1 and 56%(35/62) were current/ex-smokers. 66%(41/62) had a SPN. Mean size of largest nodule was 9mm. 11%(7/62) were diagnosed with malignancy, 6%(4/62) of pulmonary origin. The 3 non-pulmonary malignancies were renal, breast and metastatic squamous cell. New clinically important diagnoses were made in a further 11%(7/62) including TB/amyloid/ILD, whilst 78%(48/62) were benign. In the malignancy group, 71% (5/7) were current/ex-smokers, 86% (6/7) had a SPN with mean size 7.7mm and there was a higher likelihood of nodules enlarging on follow-up CTs (40% versus 2% at 2nd CT). 75%(3/4) of patients with lung malignancy underwent curative treatment. In the benign group (48), the mean number of follow-up CTs/patient (excluding baseline CT) was 1.8. 21 ultimately unnecessary investigations were performed, including 9 invasive procedures. (Table) The cost of screening to the NHS to identify a single malignancy was £5805. The cost to our service per patient screened was £655 resulting in a shortfall of £455/patient compared with the £200 charge to the PCT for an initial appointment. Conclusions: In our study, incidental nodule follow-up led to a clinically relevant diagnosis in 22% of patients, including identification of malignancy in 11%. Whilst the study had a high yield, those who received a benign diagnosis underwent a number of ultimately unnecessary investigations, some invasive, with no gain. Our 'remote management' model of care is efficient but requires an appropriate tariff.